77 PILLARS OF QUALITY AND THE PURSUIT OF EXCELLENCE a guide to basic concepts and lean six sigma tools for practitioners, managers, and entrepreneur. - Salah, Souraj ([S.l.] : PRODUCTIVITY PRESS, 2024)
This book offers a basic and practical guide for a manager, quality practitioner, or anyone interested in learning and understanding the fundamental principles, concepts, tools, and techniques of quality management and process improvement. This book enables managers to have a strong foundation for effective management and improvement of operations. It strengthens quality practitioners' approach to people, products, or services and process improvement, to influence without authority. It provides practitioners with a comprehensive understanding of the contemporary concepts of quality, guiding principles, and quality tools and techniques and on successfully implementing them. It helps enhance how practitioners perform their work and inspires them to strive for excellence. The book begins with an introduction and an overview of quality, followed by listing and explaining the selected 77 pillars (basic principles, concepts, and tools) of quality, grouped under the themes of quality, Six Sigma, and Lean Management. It examines the logical understanding of these pillars and how to implement them, providing practical examples and beneficial real case studies. The stories are based on the learning and practical experience of the author--a certified Lean Six Sigma Master Black Belt, a quality manager, and a university lecturer. This book benefits employees, partners, and customers of any organization, offering a great reference for practitioners and academics alike. It serves as a call to reflect on basic quality pillars first, before embarking on a quality improvement journey. It provides a solid foundation for managers and practitioners to exceed their customers' expectations and excel in managing their business operations.
3.9 Quality Pillar # 9: Seek Continuous Improvement. Maintain Continuity and Totality of Quality -- 3.10 Quality Pillar # 10: Imagine the Ideal State. Seek Perfection with a Bias for Action -- 3.11 Quality Pillar # 11: Innovation Is about Empathy, Collaboration, and Tolerance for Failure -- 4 Fundamental Pillars Related to Change Management -- 4.1 Quality Pillar # 12: Blame the Process, Not the People, and Do Not Shoot the Messenger -- 4.2 Quality Pillar # 13: The Root Cause of Many Problems Lies in Miscommunication
Keywords: Quality control; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Management